Bacterial adhesion of Streptococcus mutans to cobalt chromium recast alloys - Dewi Arsih Sulistiani; Widjijono Widjijono; Rini Dharmastiti (Faculty of Dentistry, Universitas Gadjah Mada, 2022)
Cobalt chromium (CoCr) alloys are utilized to make dental prosthesis. Casting CoCr alloys is a common operation in dentistry laboratories due to its low cost. Casting surplus (metal remaining in the sprue and crucible former) is frequently reused by dental laboratories to reduce and recycle metal waste. However, the quality and safety of these recast alloys require further information. Microbial attachment to the surface of metal prostheses may affect its quality and safety. Biofilm formation on metal surface can cause biocorrosion and secondary infection. The effects of different proportions of recast Cobalt Chromium alloy on the bacterial adhesion are not clear. The purpose of this study was to investigate how recasting affects the Streptococcus mutans (S. mutans) adhesion. Twenty disk-shaped specimens (n= 20, allocated for 5 groups) were prepared from CoCr alloys (Remanium GM; Dentaurum) with different proportions (100% new alloy, 25% recast alloy, 50% recast alloy, 75% recast alloy, and 100% recast alloy). After the immersion of the specimens in bacterial suspension for 24 hours, the number of bacteria that adhere to the specimen’s surface was counted using Colony Forming Units. Data were analyzed with one-way ANOVA (α = 0.05). The bacterial adhesion was significantly affected by the recast alloys (p < 0.05). An increased proportion of CoCr recast alloys showed an increase in S. mutans adhesion to the specimen surface.